The Effect of Work Environment and Job Competence on the Performance of Public Facility and Infrastructure Handling Employees (PPSU) with Work Discipline as an Intervening Variable in Sub-Districts of Jakarta Special Capital Region - Lulu Hayati Addiyar; M. Ali Iqbal (PT FORMOSA CENDEKIA GLOBAL, 2023)
This thesis was inspired by a workplace that often set unrealistically high standards for its workers without taking into account any of the elements that may be influencing their performance. Competence, Work Discipline, and Work Environment were also considered as important aspects that influenced performance in order to boost output. Employee performance was the dependent variable in this quantitative study conducted in the Sub-Districts of Jakarta Special Capital Region to test hypotheses about the influence of three independent factors (work environment, competence, and work discipline). SmartPLS 4 was used for data management on a sample size of 82 workers. The author concludes that (1) there is a favorable and substantial relationship between the work environment and work discipline. Employee performance was positively and significantly impacted by the work environment. The relationship between competence and discipline at work was a good one. A favorable and statistically significant correlation was found between employee performance and competence. Five) Workplace rules and regulations improved worker output. There was a favorable, albeit not statistically significant, relationship between work environment and employee performance. Competence positively impacted employee performance through work discipline, although the effect was not statistically significant.